Who polarises? Who targets? Parties’ educational speech over the long run - Gingrich, J; Giudici, A (Wiley, 2024)
How do political parties speak about education? While struggles over education played a foundational role in structuring modern partisan cleavages, scholars debate the extent to which parties still adopt distinct rhetorical stances on education. Existing data, however, is limited to studying broad public support or opposition to educational expansion, restricting both our empirical knowledge of the politicisation of education and our ability to theorise parties’ incentives to speak publicly about it. This paper provides the first systematic examination of the post-war evolution of partisan rhetoric about education in advanced democracies. We develop a novel dataset (Education Politics Dataset EPD) based on hand-coded manifesto speech of the largest centre-left and centre-right parties for 20 countries in Europe and beyond, from 1950 to the present. The EPD distinguishes nine educational issues, grouped under the three fundamental policy dimensions of distribution, governance and curricular content. We theorise that parties use educational speech both to signal competence to a broader electorate and to signal credibility to a narrower base. The result is three distinct patterns of speech: consensual, differentially salient and polarised. Where education policies cross-cut existing cleavages, parties devote similar attention to issues and adopt similar stances, creating a consensual pattern. We find this pattern for issues of participation and quality in education. Where education policies are universal but offer specific benefits to a partisan base, we find patterns of differential salience: some parties devote more rhetorical attention to the issue than others, but parties adopt common stances. We find this pattern for questions of spending and access. Finally, where education policies align with broader political cleavages and provide targeted electoral benefits to partisan bases, parties adopt distinct public stances leading to more polarised rhetoric. We find this pattern for issues related to academic tracking and traditional curricular content. In developing the first multidimensional theorisation and measurement of partisan rhetoric on education, the paper provides insight into parties’ evolving approaches to an area increasingly crucial to electoral and social life.